2012
DOI: 10.1134/s0021364012010031
|View full text |Cite
|
Sign up to set email alerts
|

Integration of optical pulses by resonant diffraction gratings

Abstract: Optical components for integration [1][2][3][4] and dif ferentiation [5][6][7] of optical pulses are of great interest for numerous applications including optical ultrafast information processing, optical computing, optical image recognition and coding, and formation of pulses of a specified time profile [5]. Integration (dif ferentiation) of an optical pulse is understood as inte gration (differentiation) of its envelope. At present, pulse integration and differentiation is accomplished with the use of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Ongoing studies are in line with technologies of silicon nanophotonics, aimed at creating a new generation of computer systems in which the light pulses will be used as information carriers instead of electrical signals. Doskolovich`s works theoretically prove the possibility of analog optical information processing and optical computing on the basis of resonant diffraction structures: diffraction gratings, Bragg multilayer structures, microresonators [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. In the mentioned works, it is shown that these planar diffraction structures enable performing basic operations of spatio-temporal filtering, including spatial and temporal differentiation and integration of optical signals.…”
Section: The Main Scientific Resultsmentioning
confidence: 99%
“…Ongoing studies are in line with technologies of silicon nanophotonics, aimed at creating a new generation of computer systems in which the light pulses will be used as information carriers instead of electrical signals. Doskolovich`s works theoretically prove the possibility of analog optical information processing and optical computing on the basis of resonant diffraction structures: diffraction gratings, Bragg multilayer structures, microresonators [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. In the mentioned works, it is shown that these planar diffraction structures enable performing basic operations of spatio-temporal filtering, including spatial and temporal differentiation and integration of optical signals.…”
Section: The Main Scientific Resultsmentioning
confidence: 99%
“…Soifer et al achieved several significant discoveries in this field. The pro-cesses of differentiation (integration) of the pulse envelope may be successfully conducted by employing a resonant diffraction grating, as described in studies [174][175][176][177][178][179]. High-order derivatives may be calculated quickly using a set of multiple stacked diffraction gratings [178].…”
Section: Resonant Nanophotonic Constructionsmentioning
confidence: 99%
“…A photonic crystal has a structure characterized by a spatially periodic distribution of the medium's optical properties. The spatial periodicity leads to band structure of photon dispersion [1][2][3][4][5][6][7][8], due to which the photon behavior in photonic crystals differs significantly from that in homogeneous media. The latter makes these materials potentially useful for broad range of applications, in particular, for optical waveguiding [5,6,9,10], nonlinear generation in photoniccrystalline waveguides [11,12] and fibers [13][14][15][16], novel devices based on tunable properties of the light [17][18][19][20], supercontinuum generation [21], and highly-efficient nonlinear light conversion [22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%